The Relationship of Tutor Interpersonal Communication with Package C Student Learning Outcomes at PKBM Farillailmi Padang City - Muhammad, Afandi; Irmawita, Irmawita (Universitas Negeri Padang, 2024)
This study was motivated by the poor academic performance of Group C trainees at PKBM Farila Ilmi Padang City. This is attributed to the tutor's interpersonal communication. The purpose of this study was (1) to describe the interpersonal communication of tutors, (2) to describe the learning outcomes of the learning community, and (3) to examine the relationship between the communication among the tutors. individual tutors and learning outcomes from the learning community. . Meet. This study included a quantitative correlation study. The population studied was Ms. Farila Ilmi, resident of PKBM Package C. Technical data were collected using a questionnaire designed in the form of a questionnaire. Data analysis technique using percentage formula and product time correlation formula. As a result, (1) the tutor's interpersonal communication is still ineffective, (2) the student achievement at PKBM Farila Ilmi is low, and (3) there is a significant difference between the communication between students. individual tutors and student learning outcomes. It has been shown that there is a significant correlation between students.Keywords: learning Outcomes, Interpersonal Comunication